Sagot :
Answer:
An = 6n - 7
Step-by-step explanation:
Given: (3,11) and (6,23)
The formula of Arithmetic sequence
- An = A1+(n-1)d
For (3,11)
- A(3) = A1 + (3-1)d
- 11 = A1 + 2d
For (6,23)
- A(6) = A1 + (6-1)d
- 23 = A1 + 5d
Subtract the two solved equations:
23 = A1+5d
- 11 = A1 + 2d
------------------------------
= 12 = +2d
12/2 = d
6 = d
Now , we solve for the A1 by substituting the values
- An = A1 + (n-1)d
- A(3) = A1 + (3-1)6
- 11 = A1 + 2(6)
- 11 = A1 + 12
- 11 - 12 = A1
- - 1 = A1
Again , we know that
- An = A1+(n-1)d
We therefore substitute the value of d and A1 to get the general rule
- An = -1 + (n-1)6
- An = -1 + 6n-6
- An = 6n - 7